PRESTASI BELAJAR SISWA DALAM DIKLAT LESSON STUDY - Indrawan, Putu Oktap (Jurnal Pendidikan Indonesia, 2017)
The aims of this study were: (1) to describe the quality of the workshop of lesson study on science teachers at SMKN 2 Seririt; and (2) to analyze the differences of the student’s learning achievement in science subject before and after workshop of lesson study at SMKN 2 Seririt. This study was a pre-experimental study using one group pretest-postest design. The population of this study were focused on eleventh grade students of SMKN 2 Seririt in the academic year 2013/2014. The samples of the class for this study was determined by random sampling technique. The data were analyzed by descriptive statistics and hipotesis analyzed by paired sample t-test  for the data of student’s achievement in science subject. The result showed that: (1) the workshop of lesson study on science teachers at SMKN 2 Seririt fell into very good qualification ( 91,781); and (2) there were significant differences of the student’s learning achievement in science subject before and after workshop of lesson study (t=123,8493; p<0,05).